Mentoring : a sustainable means of developing young leaders for the church in Africa - Chiroma, Nathan Hussaini (Stellenbosch : Stellenbosch University, 2008)
Thesis (MTh (Practical Theology and Missiology))--Stellenbosch University, 2008.